The homozygous variant c.797G>A/p.(Cys266Tyr) in PISD is associated with a Spondyloepimetaphyseal dysplasia with large epiphyses and disturbed mitochondrial function. Issue 3 (21st December 2018) - Girisha, Katta M.; von Elsner, Leonie; Neethukrishna, Kausthubham; Muranjan, Mamta; Shukla, Anju; Bhavani, Gandham SriLakshmi; Nishimura, Gen; Kutsche, Kerstin; Mortier, Geert
Abstract: Spondyloepimetaphyseal dysplasias (SEMD) are a group of genetically heterogeneous skeletal disorders characterized by abnormal vertebral bodies and epimetaphyseal abnormalities. We investigated two families with a new SEMD type with one proband each. They showed mild facial dysmorphism, flat vertebral bodies (platyspondyly), large epiphyses, metaphyseal dysplasia, and hallux valgus as common clinical features. By trio‐exome sequencing, the homozygous missense variant c.797G>A/p.(Cys266Tyr) in PISD was found in both affected individuals. Based on exome data analyses for homozygous regions, the two patients shared a single homozygous block on chromosome 22 including PISD, indicating their remote consanguinity. PISD encodes phosphatidylserine (PS) decarboxylase that is localized in the inner mitochondrial membrane and catalyzes the decarboxylation of PS to phosphatidylethanolamine (PE) in mammalian cells. PE occurs at high abundance in mitochondrial membranes. Patient‐derived fibroblasts showed fragmented mitochondrial morphology. Treatment of patient cells with MG‐132 or staurosporine to induce activation of the intrinsic apoptosis pathway revealed significantly decreased cell viability with increased caspase‐3 and caspase‐7 activation. Remarkably, ethanolamine (Etn) supplementation largely restored cell viability and enhanced apoptosis in MG‐132‐stressed patient cells. Our data demonstrate that the biallelic hypomorphic PISD variant p.(Cys266Tyr) is associated with a novel SEMD form, which may be treatable with Etn administration. Abstract : Trio exome sequencing in two different families with one child each with short stature, platyspondyly and large epiphyses revealed a shared homozygous missense variant c.797G>A/p.(Cys266Tyr) in PISD. Studies on patient‐derived fibroblasts confirmed the pathogenicity of this variant suggesting that the children have a new form of spondyloepimetaphyseal dysplasia.